Pressure induced effects on the chemical and magnetic structure of spinel MnV2O4. (31st July 2017) - Singh, Ripandeep; Hansen, T; Ritter, C; Sharma, Neetika; Shahi, P; Chatterjee, S; Das, A
Abstract: The influence of external pressure ( P ⩽ 5 GPa) on both the structural and magnetic ordering in MnV2 O4 has been investigated using neutron diffraction technique. The volume and the V–V distance decrease with pressure while the c / a ratio increases, suggesting a lowering of the distortion with pressure. Under ambient conditions this compound exhibits a structural transition ( T S ) from tetragonal to cubic at 53 K and a magnetic transition ( T N ) at 56 K. It is found that with an increase in pressure to 5 GPa, T N increases (from 56 K to 80 K), d T N /d P > 0, while T S decreases (from 53 K to 37 K). The non collinear magnetic structure in the tetragonal phase at 5 GPa and 10 K remains the same as at ambient pressure. However, the Mn and V sublattice, now exhibits distinct transition temperatures, T N M n 80 K, and T N V 60 K. The transition to the cubic phase at T S is accompanied by a collinear alignment of the Mn and V spins and a reduction in the Mn moment. The region in which the structure remains in the cubic phase with collinear magnetic structure increases with pressure from 3 K at ambient pressure to 43 K at 5 GPa pressure.